Pengembangan E-LKPD Berbasis Inkuiri pada Materi Menganalisis Struktur Teks Negosiasi di Kelas X SMA Negeri 1 Gunungsitoli - Eunike Pratiwi Harefa; Noveri Amal Jaya Harefa (Indo-MathEdu Intellectuals Journal, 2023)
Teaching materials are a tool to assist teachers and students in carrying out learning activities. However, the teaching materials used are still limited to package books only, making students less active in learning. The purpose of this research is to develop teaching materials in the form of inquiry-based E-LKPD on the material of analyzing the structure of negotiation text in class X SMA Negeri 1 Gunungsitoli. The method used in this research is Research and Development (R&D). The development model used is ADDIE which consists of analysis, design, development, implementation, and evaluation stages. Based on the results of the study, the E-LKPD product obtained very valid criteria 99% material validators, 93% language validators and 96% design/media validators. It is stated that it is very practical obtained from the students' response questionnaire, namely individual trials of 92.8%, small group trials of 96.4% and field trials of 94.9%. Furthermore, it was declared very effective obtained from the learning test results, namely individual trials with classical completeness of 100%, small group trials of 83.3% and field tests of 95.8%. From the research results above, the inquiry-based E-LKPD developed has met the criteria of valid, practical, and effective for use in Indonesian language learning